2022
DOI: 10.1097/mao.0000000000003702
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient Barriers to Cochlear Implantation

Abstract: Objective: Evaluate barriers that deter adult patients from following through with cochlear implantation. Study Design: Retrospective chart review and phone survey. Setting: Single tertiary referral center. Patients: Between January 2019 and August 2021, 113 patients, without a previous cochlear implant (CI), were determined to be candidates for cochlear implantation. Thirty-eight (33.6%) patients deferred cochlear implantation. Survey response rate was 61.1% (22/36). Intervention: None. Main Outcome Measures:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The proportion of individuals in our population who were cochlear implant candidates (91.9%) and who underwent surgery (89.9%) are higher than many others in the literature (rates of nonqualification ≤37% and rates of surgical deferral ≤38%) . This may be due to unmeasured differences in the demographics of our patient population—including race and ethnicity (which were not collected in our study), employment, and prior hearing aid use, all of which affect rates of cochlear implant qualification and surgical pursuance—or differences in our center’s threshold for cochlear implant evaluation referral .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The proportion of individuals in our population who were cochlear implant candidates (91.9%) and who underwent surgery (89.9%) are higher than many others in the literature (rates of nonqualification ≤37% and rates of surgical deferral ≤38%) . This may be due to unmeasured differences in the demographics of our patient population—including race and ethnicity (which were not collected in our study), employment, and prior hearing aid use, all of which affect rates of cochlear implant qualification and surgical pursuance—or differences in our center’s threshold for cochlear implant evaluation referral .…”
Section: Discussionmentioning
confidence: 73%
“…The proportion of individuals in our population who were cochlear implant candidates (91.9%) and who underwent surgery (89.9%) are higher than many others in the literature (rates of nonqualification ≤37% and rates of surgical deferral ≤38%). 11,13,40,[44][45][46][47][48][49] This may be due to unmeasured differences in the demographics of our patient population-including race and ethnicity (which were not collected in our study), employment, and prior hearing aid use, all of which affect rates of cochlear implant qualification and surgical pursuance-or differences in our center's threshold for cochlear implant evaluation referral. 11,13 The median candidacy AzBio in quiet score among our entire evaluated cohort was lower than among other populations in the literature with higher nonqualification and surgical deferral rates; for example, in one study with an 18% surgical deferral rate, 40 the mean candidacy AzBio in quiet score among those who pursued surgery was 23.3%.…”
Section: Limitationsmentioning
confidence: 99%
“…Mangan et al (14) looked at patients out of the St. Louis, Missouri, and Little Rock, Arkansas, who deferred cochlear implantation and why they did so. Their study found a deferral rate of 33.6%, which is nearly double our rate of 16.2%.…”
Section: Discussionmentioning
confidence: 99%
“…2 Once patients have undergone CI evaluation and qualify for surgery, as many as 20%-50% ultimately decide against implantation, further limiting implantation rates. [6][7][8] This study aimed to gain insight on patients at risk of deferring CI surgery in the context of socioeconomic factors. We found that age, race, and marital status were critical factors in predicting surgery after being deemed CI candidates.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 Furthermore, once patients qualify for implantation, up to 20%-50% ultimately elect against surgery. [6][7][8] This occurs despite mounting evidence linking hearing loss to cognitive decline and dementia, social isolation and depression, decreased employability, and increased risk of falls and hospitalizations. [9][10][11] The economic impact of hearing loss in the US is significant, with excess medical costs ranging between $3.3-12.8 billion.…”
Section: Introductionmentioning
confidence: 99%